Pre-pregnancy preparation in women with polycystic ovary syndrome and obesity: state-of-the-art - I.A. Lapina; T.G. Chirvon; Yu.E. Dobrokhotova; V.V. Taranov (LCC «Medicine-Inform», 2021)
I.A. Lapina, T.G. Chirvon, Yu.E. Dobrokhotova, V.V. Taranov Pirogov Russian National Research Medical University, Moscow, Russian Federation In recent decades, extensive growth in the number of overweight or obese individuals is reported thus making this issue important for the medical community. According to some authors, 8% of overweight women and 18% of obese women have troubles with realizing reproductive function. Glucose and lipid metabolism disorders and hypertension that are common in women with polycystic ovary syndrome (PCOS) allow for referring this condition to metabolic diseases. Metabolic syndrome is an umbrella term for a set of metabolic abnormalities arising from insulin resistance and hyperinsulinemia. PCOS may also be considered as one of its manifestations being regarded as the most common cause of infertility in overweight and obese women. The treatment should be complex to recover reproductive function and to address metabolic disorders. Adherence to lifestyle changes, diet, and regular physical activity is still poor. Therefore, the use and assessment of the efficacy of pharmaceutical s for pre-pregnancy preparation to lose weight and to improve reproductive outcomes in PCOS. Keywords: polycystic ovary syndrome, PCOS, obesity, metabolic syndrome, infertility, pre-pregnancy preparation, treatment, prevention, ovulation. For citation: Lapina I.A., Chirvon T.G., Dobrokhotova Yu.E., Taranov V.V. Pre-pregnancy preparation in women with polycystic ovary syndrome and obesity: state-of-the-art. Russian Journal of Woman and Child Health. 2021;4(2):137-143. DOI: 10.32364/2618-8430-2021-4-2-137-143.